Immiscible Displacements and Capillary Trapping in CO2 Storage - Pentland, C.; El-Maghraby, R.; Georgiadis, A.; Iglauer, Stefan; Blunt, M. (ICGGCT, 2010)
We measure the residual non-wetting phase saturation of super-critical carbon dioxide in a Berea sandstone core. We use the porous plate method while a stirred reactor ensures equilibrium between the carbon dioxide and brine. We also measure carbon dioxide-brine contact angles on the porous plate to understand wetting behavior in the experiment. The application of the work is for carbon dioxide storage in aquifers, where capillary trapping is a rapid and effective mechanism to render the injected fluid immobile. The experiment was performed at temperature and pressure representative of potential subsurface storage formations. The measured residual saturation is 37% which is lower than the measured residual for an oil-brine system on a similar core (48%), but higher than measured by other authors for super-critical CO2 in Berea sandstone. We suggest that super-critical CO2 is still non-wetting in sandstones with considerable trapping and discuss the implications for CO2 storage in aquifers.